APPROBATION OF THE PROGRAM FOR OVERCOMING NEGATIVE MENTAL STATES IN ENTREPRENEURS DURING THE WAR AND ITS EFFECTIVENESS (Psychology Travelogs, 2024)
According to the results of a comparative analysis of the indicators of the methods of the control and experimental groups of entrepreneurs regarding the manifestations of negative mental states after the application of the program to overcome them, the following was found.Firstly, it was determined that according to the method of «Self-assessment of mental states» by H. Aizenko, indicators of anxiety and aggressiveness significantly decreased, with a downward trend observed in the final assessment of mental states.Secondly, according to the method of «Differential diagnosis of depressive states» by V. Zhmurov, a significant decrease in the negative impact on the scales of apathy, hypothymia, dysphoria and confusion was determined.Thirdly, positive changes were revealed by the results of the «Entrepreneurial Motivation» method by L. Karamushka and L. Khudyakova: direct motives rose to an average level, which led to a significant increase in the final assessment of basic motives, which significantly dominate over indirect motives.Fourthly, based on the evaluation of the symptoms and phases of professional burnout among entrepreneurs, it was determined that in the stress phase, the indicators of symptoms of experiencing psycho-traumatic circumstances, «backed into a corner» significantly decreased; in the resistance phase, inadequate selective emotional reaction and emotional and moral disorientation significantly decreased; in the phase of exhaustion, the rate of emotional deficit of the individual and emotional alienation decreased in the entrepreneurs of the experimental group.Fifthly, according to O. Kokun's «Professional Vitality» methodology, it was established that the effectiveness of the application of the program is manifested in the improvement from a low level in the control group to the average level in the experimental components of vitality.
Keywords: approbation; program; effectiveness; negative mental states; entrepreneurs; war